Critical success factors of expatriation by Malaysian international corporations / Awang Rozaimie Awang Shuib, Senian Malie and lsma Izza Mohd Esa - Awang Shuib, Awang Rozaimie; Malie, Senian; Mohd Esa, lsma Izza (Research Management Institute (RMI), 2008)
Globalization is fuelling competition f or international expansion. As firms move from creating new products and services to marketing, this effort requires increased expatriation to achieve global business goals. This study identifies critical success factors (CSF) relating to expatriation by Malaysian corporations operating internationally and identifies a number of strategies that can be adopted by these corporations to enhance their viability overseas. In addition, this study reviews current issues related to expatriation and identifies and ranks factors that contribute to the success or failure of expatriation by Malays ian corporations. Self-a dministered questionnaires were developed to collect the primary data, yielding a response rate of 35. 2 percent. The results indicate that most Malaysian manufactur ers are involved in expatriation activities. The ability to work in international teams was identified and ranked as the most important factor in determining the effectiveness of expatriation. Language proficiency ranked next in importance. In addition, adaptability to the international assignment and expatriate sensitivity to cultural elements were considered important to the success or failure of an international assignment. Results support previous research with regard to the importance ofan effective expatriation selection process in order for a companys international expansion strategy to succeed.